Pythium myriotylum Is Recovered Most Frequently from Pythium Soft Rot-Infected Ginger Rhizomes in China - Daly, Paul (Plant disease, 2022)
Pythium soft rot is a major soilborne disease of crops such as ginger (Zingiber officinale). Our objective was to identify which Pythium species were associated with Pythium soft rot of ginger in China, where approximately 20% of global ginger production is located. Oomycetes infecting ginger rhizomes from seven provinces were investigated using two molecular markers, the internal transcribed spacer, and cytochrome c oxidase subunit II (CoxII). In total, 81 isolates were recovered; approximately 95% of the isolates were identified as Pythium myriotylum, and the other isolates were identified as either P. aphanidermatum or P. graminicola. Notably, the P. myriotylum isolates from China did not contain the single nucleotide polymorphism in the CoxII sequence found previously in the P. myriotylum isolates infecting ginger in Australia. A subset of 36 isolates was analyzed repeatedly by temperature-dependent growth, severity of disease on ginger plants, and aggressiveness of colonization on ginger rhizome sticks. In the pathogenicity assays, 32 of 36 isolates were able to significantly infect and cause severe disease symptoms on the ginger plants. A range of temperature-dependent growth, disease severity, and aggressiveness in colonization was found, with a significant moderate positive correlation between growth and aggressiveness of colonization of the ginger sticks. This study identified P. myriotylum as the major oomycete pathogen in China from infected ginger rhizomes and suggested that P. myriotylum should be a key target to control soft rot of ginger disease